Clinical characteristics of infantile haemangioma in twins: a retrospective study - Zhengwei Sun; Miaomiao Li; Changxian Dong; Shiwei Mei (BMC, 2024)
Abstract Background Infantile hemangioma is one of the most common benign soft tissue tumors in infants. The pathogenesis of infantile hemangioma remains unclear and twin studies regarding its incidence may help clarify disease pathogenesis. Thus, this study aimed to analyze the clinical characteristics of infantile hemangioma in twin patients and discuss its clinical incidence. Methods We retrospectively analyzed the data of 83 pairs of twins with infantile hemangioma admitted to the Guangdong Provincial Women and Children Hospital and Henan Provincial People's Hospital between May 2016 and May 2022. Thirty-one pairs of twins among whom both developed infantile hemangioma and 52 pairs of twins among whom only one twin was affected were included. Analysis was performed using the Spearman correlation. Additionally, we analyzed the influence of factors such as sex, twin zygosity, preterm birth, birth weight, and assisted reproduction on the clinical characteristics of twins. Results We observed that disease occurrence in both twins correlated with assisted reproduction (χ2 = 13. 102, P < 0.05) and preterm birth (χ2 = 36.523, P < 0.05). Twin zygosity (χ2 = 0.716, P > 0.05) and total birth weight of twins (t=-3.369, P > 0.05) were not correlated with infantile hemangioma. However, among twins, the ones with lesser birth weight were more likely to develop infantile hemangioma. Conclusions The clinical characteristics of infantile hemangioma in twins were consistent with their epidemiological characteristics. Female sex, preterm birth, less birth weight, and assisted reproduction increased the probability of morbidity in both twins. Analysis of the characteristics of infantile hemangioma in twins may assist further research and clinical treatment.